Exercise attenuates high-fat diet-induced PVAT dysfunction through improved inflammatory response and BMP4-regulated adipose tissue browning - Liu, Xiaojie; Jiang, Xi; Hu, Jing; Ding, Mingxing; Lee, Sang Ki; Korivi, Mallikarjuna; Qian, Yongdong; Li, Ting; Wang, Lifeng; Li, Wei (Frontiers in Nutrition, 2024)
Background: Perivascular adipose tissue (PVAT) dysfunction impairs vascular homeostasis. Impaired inflammation and bone morphogenetic protein-4 (BMP4) signaling involved in thoracic PVAT dysfunction by regulating adipokine secretion and adipocyte phenotype transformation. We investigated whether aerobic exercise training could ameliorate high-fat diet (HFD)-induced PVAT dysfunction via improved inflammatory response and BMP4-mediated signaling pathways. Methods: Sprague-Dawley rats (n=24) were assigned into control, high-fat diet (HFD), and HFD plus exercise (HEx) groups. After 6-week intervention, PVAT functional efficiency and changes in inflammatory biomarkers (circulating concentrations in blood and mRNA expressions in thoracic PVAT) were assessed. Results: Chronic HFD feeding caused obesity and dyslipidemia in rats. HFD decreased relaxation response of PVAT-containing vascular rings and impaired PVAT-regulated vasodilatation. However, exercise training effectively reversed these diet-induced pathological changes to PVAT. This was accompanied by a significant (p < 0.05) restoration of morphological structure and decreased lipid droplet size in PVAT. Furthermore, HFD-induced impaired inflammatory response (both in circulation and PVAT) was notably ameliorated by exercise training (p < 0.05). Specifically, exercise training substantially reversed HFD-induced WAT-like characteristics to BAT-like characteristics as evidenced by increased UCP1 and decreased FABP4 protein levels in PVAT against HFD. Exercise training promoted transcriptional activation of BMP4 and associated signaling molecules (p38/MAPK, ATF2, PGC1α and Smad5) that are involved in browning of adipose tissue. In conjunction with gene expressions, exercise increased BMP4 protein content, and activated downstream cascades, represented by upregulated p38/MAPK andPGC1α proteins in PVAT. Conclusions: Regular exercise training can reverse the HFD-induced obesity, dyslipidemia and thoracic PVAT dysfunction in rats. The browning of adipose tissue by exercise appears to be modulated through improved inflammatory response and/or BMP4-mediated signaling cascades in obese rats.